Persepsi Inovasi Produk Pembiayaan Syariah dan Minat Mengakses Bank Syariah: Studi Survei Pendahuluan di Desa Meureubo, Aceh Barat - Nurul Fajriatul Muqhni A; Muliza Muliza; Mikhral Rinaldi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This pilot survey examines perceptions of Islamic financing product innovation and intention to access Islamic banking among residents of Meureubo Village, West Aceh, Indonesia. A cross-sectional descriptive-exploratory design was used. A five-point Likert questionnaire was administered to 20 respondents (10-24 June 2025) who were users or prospective users of Islamic financing. Constructs covered perceived process ease, variety of contracts/schemes, need-fit, value-fit, self-reported contract understanding, socialization/information exposure, and intention. Results indicate positive perceptions: all respondents agreed that the products are easy to understand and fit needs and Islamic values. Intention was high; 90% reported that innovation increases their interest in using Islamic banking. However, 70% identified limited outreach/socialization as a barrier, and 30% were neutral about simpler application procedures. The findings suggest that product innovation should be accompanied by communication innovation—contract literacy, community-based outreach, and simulations—to translate interest into actual access. As a pilot, results map priority indicators for larger studies.